PERAN PENDIDIKAN IPS DALAM MEMPERSIAPKAN SISWA MENGHADAPI TANTANGAN DI ERA GLOBALISASI - Tanjung, Pariatman (Universitas Tanjungpura, 2024)
Globalization has had a significant impact on various aspects of life, including education. The rapid development of technology and communication has formed a global network that has changed the lifestyle of people throughout the world. However, globalization also poses challenges, especially in terms of morality, cultural identity and nationalism of the younger generation. This research aims to examine the role of social studies education in facing these challenges. The research method used is library research, by analyzing various relevant literature. The research results show that social studies education has an important role in equipping students with a critical understanding of the impact of globalization, as well as in maintaining moral values, cultural identity and nationalism among students. Effective social studies education can function as a bulwark in maintaining morality and cultural identity amidst globalization. Therefore, innovation is needed in social studies learning, especially through the integration of technology and reconstruction of teaching methods to make them more relevant to the demands of the 21st century. Social studies education is not only a means of transferring knowledge, but also an important means of shaping the character and identity of the younger generation in the era of globalization.